Implementation of Data Mining Algorithm C4.5 (Decision Tree) Product Distribution at PT.XYZ - Wulan Dari; Raden Aris Sugianto (Lembaga Pengembangan Kinerja Dosen, 2025)
PT. XYZ in its distribution is still carried out by using the sales and the results of sales or distribution are recorded in a ledger about how many cigarette products are sold, as well as biodata from consumers. Based on the results of recording in the field will be recapitulated again at the office by using Microsoft Excel this is very difficult in the process of data integration, manufacturing, suppliers, retailers, sales and distribution of products. One of the things that can support the efficiency of production activities is to set the layout of the production machines owned. Material handling process, space utilization, distance between departments, production process flow can be more efficient if good layout planning is done. Supply Chain Management (Supply Chain Management) is a field of study that lies in the efficiency and effectiveness of the flow of cigarettes, information, and money flows that occur simultaneously so that it can unite the Supply Chain Management with the parties involved. The results of this study are a distribution information system that can be used to record all sales transactions. In order to make it easier for the data distribution section manager to recap and know the history of cigarette distribution better and complete reporting.